In the company of cars : driving as a social and cultural practice - Redshaw, Sarah, 1958- (Human factors in road and rail transport., 2008)
Road safety research has traditionally involved a focus on individuals in which social norms are considered but rarely discussed in detail. Outlining the existing body of research on young drivers in particular, In the Company of Cars shows the contribution that considering road safety from a social and cultural perspective could make to the reduction of death and injury on the roads. It highlights the involvement of driving cultures, as distinct from car cultures, in the social framing of cars and the ways in which they are utilised.